Bispidine coordination chemistry - Bleher, Katharina; Cieslik, Patrick; Comba, Peter (Dalton transactions, 2025)
Bispidines are extremely rigid ligands, easy to prepare in a large variety, with denticities of four to ten, various donor sets and charges, for mono- and oligonuclear transition metal, main group and rare earth complexes. In the last approx. 20 years significantly more than 50 new bispidine based ligands were prepared and their coordination chemistry studied. Biological probes and medicinal applications is one main area in bispidine coordination chemistry, where fast complex formation, high stability, metal ion selectivity and inertness are of utmost importance. Oxygen activation and oxidation catalysis is another main focus in bispidine coordination chemistry, with catalyst efficiency and stability as well as product selectivity as important requirements. Particularly successful applications in these areas are presented and discussed in detail, in addition to fundamental principles that show the importance of ligand rigidity, cavity size and shape as overarching fundamental properties.